Association of adiponectin/leptin ratio with carbohydrate and lipid metabolism parameters in HIV-infected patients during antiretroviral therapy. (3rd July 2018) - Tiliscan, Catalin; Arama, Victoria; Mihailescu, Raluca; Munteanu, Daniela; Iacob, Diana Gabriela; Popescu, Cristina; Catana, Remulus; Negru, Anca; Lobodan, Alina; Arama, Stefan Sorin
ABSTRACT: Background : Adiponectin and leptin are adipose tissue hormones that regulate important lipid and glucose metabolic pathways. Our objective was to evaluate the interplay of these hormones described by the adiponectin/leptin ratio (ALR) in correlation to lipid and carbohydrate metabolism parameters in nondiabetic HIV-infected patients during antiretroviral therapy (ART). Materials and Methods : We enrolled consecutive nondiabetic patients with confirmed HIV infection, undergoing stable ART regimens for at least six months. Blood samples were collected and tested for immunological and virological parameters, adiponectin and leptin, fasting insulin, fasting plasma glucose, fasting triglycerides, total cholesterol, LDL cholesterol, and HDL cholesterol. ALR was computed for each patient. Resistance to insulin was assessed by calculating the Quantitative Insulin Sensitivity Check Index (QUICKI). Results : We enrolled 87 HIV-infected persons, with a mean age of 31.7 years (range: 18–65), including 47 men (mean age = 32.8 years) and 40 women (mean age = 30.5 years). The median value of ALR was 6.8 (interquartile range – IQR = 17.1). In male patients, ALR was inversely associated with the serum level of triglycerides (R = 0.285, p  = 0.05), total cholesterol (R = 0.326, p  = 0.02), and LDL cholesterol (R = 0.298, p  = 0.04). Also for the male cohort, an increase in ALR seemed to improve insulin sensitivity (R = 0.323, p  = 0.02) and serum HDL cholesterol (R = 0.597, p  = 0.01). None of these correlations were observed in HIV-infected women. Conclusion : Adiponectin and leptin seem to play important but different gender-specific roles in the pathogenesis of lipid and glucose metabolism of HIV-infected patients undergoing antiretroviral therapy. Abbreviations : ALR, adiponectin/leptin ratio; BMI, body mass index; LDL, low-density lipoprotein; HDL, high-density lipoprotein; QUICKI, Quantitative Insulin Sensitivity Check Index.